Application of lidar technology to predict wind resource for modern wind turbines. Issue 1 (31st December 2022) - Sharma, Pramod Kumar; Warudkar, Vilas; Ahmed, Siraj
ABSTRACT: Prediction of wind resource potential for a site is crucial to assess any wind farm. However, this can be done by installing long and costly meteorological masts with different wind sensors. This work utilises the application of remote sensing techniques to predict wind resources near the coastal offshore site at Dhanushkodi, near Rameshwaram. This paper is divided into two sections: First, four types of wind speed extrapolating models have been used to predict wind speed at higher heights, the predicted wind speeds are compared with the actual wind speed data recorded by mast and lidar. Second: comparative analyses of Weibull parameters derived from maximum likelihood and modified maximum likelihood methods have been observed using the same extrapolation models at the same heights. The R 2 and RMSE for wind speed and direction at different observed heights were equal to or higher than 0.95 and 0.1426 respectively at Dhanuskhkodi.